2021
DOI: 10.1111/hex.13345
|View full text |Cite
|
Sign up to set email alerts
|

Participatory codesign of patient involvement in a Learning Health System: How can data‐driven care be patient‐driven care?

Abstract: Background: A Learning Health System (LHS) is a model of how routinely collected health data can be used to improve care, creating 'virtuous cycles' between data and improvement. This requires the active involvement of health service stakeholders, including patients themselves. However, to date, research has explored the acceptability of being 'data donors' rather than considering patients as active contributors. The study aimed to understand how patients should be actively involved in an LHS.Design: Ten parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
(73 reference statements)
0
20
0
Order By: Relevance
“…If health research is to benefit from experiential knowledge, public collaborators need testimonial justice. What they say needs to be taken as worthy of influencing the research 12 . Sociologists have had a longstanding interest in people's everyday ideas about health and illness 13–15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If health research is to benefit from experiential knowledge, public collaborators need testimonial justice. What they say needs to be taken as worthy of influencing the research 12 . Sociologists have had a longstanding interest in people's everyday ideas about health and illness 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…What they say needs to be taken as worthy of influencing the research. 12 Sociologists have had a longstanding interest in people's everyday ideas about health and illness. 13 , 14 , 15 These ideas have been explored in the context of public health and healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…These measures potentially influence QI interventions, but this study corroborates previous research3 30 and illustrates significant opportunity for improvement. Earlier research indicates that hospital professionals do not request large amounts of data as they need only the relevant data for guidance, recommendations and prioritisation of each case 40. Patient-reported measures must help professionals focus on what matters most in QI rather than overwhelm them with information or demanding administration.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were crucial to capturing what tools might work in practice as they were on site. Published studies have similarly reported on the richness that emerges in the research and partnership from adopting PPIE in co-design [ 32 , 33 ]. Our work resonates with the reciprocal learning reported emphasising the importance of building the foundations for relationships, fostering trust, respect, creating a safe space, to talk about the research and the effects on the partnership [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…When designing digital health interventions, these should equally be based on patient and carer experiences [ 29 31 ]. Finally, PPIE in co-design is context dependent [ 32 , 33 ] and thus it is important to outline the approach taken in the co-design of an intervention.…”
Section: Introductionmentioning
confidence: 99%